BF061, a novel antiplatelet and antithrombotic agent targeting P2Y12 receptor and phosphodiesterase - Hu, Liang; Fan, Zhichao; Du, Hongguang; Ni, Ran; Zhang, Si; Yin, Kanhua; Ye, Jianqin; Zhang, Yan; Wei, Xunbin; Zhang, Xiaohui; Gross, Peter L.; Kunapuli, Satya P.; Ding, Zhongren (Thrombosis and Haemostasis, 2011)
The addition of phosphodiesterase (PDE) inhibitors has been reported to potentiate the antithrombotic effects of P2Y12 antagonists without increasing bleeding risk. In this study, we report that a potent antiplatelet agent, 2-ethylthio-6-phenethylaminoadenosine (BF061), inhibits platelet activation and thrombosis via P2Y12 antagonism and PDE inhibition. We explored the antiplatelet mechanism of BF061 by measuring cAMP, cGMP levels, PDE activity, and the interaction between ADP and P2Y12 using atomic force microscopy. The antithrombotic effect of BF061 was evaluated in mice using intravital microscopy in FeCl3-induced mesenteric and laser-induced cremasteric arterial thrombosis models. BF061 robustly inhibited platelet aggregation and ATP release induced by multiple platelet agonists via P2Y12 antagonism and PDE inhibition. Interestingly, despite being structurally similar to BF061, P2Y12 receptor antagonist AR-C69931MX had no effect on human platelet PDE. In FeCl3-induced mesenteric arterial thrombosis model, BF061 effectively prevented thrombus formation similarly to clopidogrel; it also reduced thrombus volume in laser-injured cremaster arteriole model. In contrast, BF061 induced dramatically less bleeding at an antithrombotic dose compared to clopidogrel. In summary, we developed a novel antiplatelet and antithrombotic agent targeting both P2Y12 and PDE. Given the prevalence of combined antiplatelet therapy in clinical practice, an antiplatelet agent bearing dual activities may have therapeutic advantage as a potential antithrombotic drug.
Keywords: Antiplatelet; antithrombotic; BF061; PDE inhibitor; P2Y12 receptor antagonist